2020
DOI: 10.1074/jbc.ra120.013508
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcated binding of the OmpF receptor underpins import of the bacteriocin colicin N into Escherichia coli

Abstract: Colicins are Escherichia coli–specific bacteriocins that translocate across the outer bacterial membrane by a poorly understood mechanism. Group A colicins typically parasitize the proton-motive force–linked Tol system in the inner membrane via porins after first binding an outer membrane protein receptor. Recent studies have suggested that the pore-forming group A colicin N (ColN) instead uses lipopolysaccharide as a receptor. Contrary to this prevailing view, using diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Integrating the localization of islands from a population of stationary phase cells clearly indicated that they were mostly localized in polar regions (Figure 3C). To confirm the apparent polar localization of BamA in stationary phase was not an artefact of epitope accessibility, for example due to changes in cell surface topology (52), cells were co-labelled with both αBamA AF488 and ColN −mCherry (54) which binds with high affinity to OmpF. Although OmpF distribution was slightly polar biased, it was labelled across the cell and the correlation between the fluorescent intensities of the two labels was poor (Figure S4D-E), suggesting that labelling accessibility was not the reason for the non-uniform distribution of BamA.…”
Section: Resultsmentioning
confidence: 99%
“…Integrating the localization of islands from a population of stationary phase cells clearly indicated that they were mostly localized in polar regions (Figure 3C). To confirm the apparent polar localization of BamA in stationary phase was not an artefact of epitope accessibility, for example due to changes in cell surface topology (52), cells were co-labelled with both αBamA AF488 and ColN −mCherry (54) which binds with high affinity to OmpF. Although OmpF distribution was slightly polar biased, it was labelled across the cell and the correlation between the fluorescent intensities of the two labels was poor (Figure S4D-E), suggesting that labelling accessibility was not the reason for the non-uniform distribution of BamA.…”
Section: Resultsmentioning
confidence: 99%
“…The main biological function of ColN is to kill bacterial cells by forming an ion channel in the inner membrane of susceptible bacteria [31] . Its mechanism of action requires all three domains to mediate bacterial cell death; i) R domain binds to outer membrane protein F and lipopolysaccharides (LPS) on the bacterial cell surface [50] , [51] , ii) T domain interacts with receptors to trigger the translocation of P domain across bacterial membranes [52] , and iii) P domain generates the pore causing ion leakage [53] . The spot test assay in this study revealed that the bactericidal activity of ColN +12 was weaker than that of ColN WT .…”
Section: Discussionmentioning
confidence: 99%
“…The transport varies according to the size, charge and hydrophilicity of the molecule. Recently, the dual function of the porin OmpF both as receptor and translocator for the pore-forming colicin N, has been elegantly demonstrated (Jansen et al, 2020). However, more hydrophobic or higher molecular mass compounds above the porin threshold require other strategies, among which hijacking receptors or transporters required for vital functions is a major one.…”
Section: The Uptake Systemsmentioning
confidence: 99%